The influence of iman, Islam and ihsan towards the self well-being - Mohd Nasir Masroom; Siti Norlina Muhamad; Siti A'isyah Panatik @ Abd Rahman (Penerbit Universiti Kebangsaan Malaysia, 2017)
Islam is a religion that brings blessings to the entire world. It is built from three major componentsthat derive to perfection of Islam, i.e. Iman, Islam and Ihsan. These components should be integrated, understood and practiced by every Muslim. This integration will shape the character of Muslims who obey to Allah, and serves as a good member of society. However, how far all these components affected the lives of Muslims? This article describes the influences of Iman, Islam and Ihsan towards the development of the self well-being. This article was conducted in descriptive based on the Quran and the Hadith. The article found that all three components had positive influences to Muslim self well-being. However, these influences are limited to Muslim who really believe, understand and appreciate the principles integratively. In addition, the practices are one of the prime conditions to obtain the positive influences. In Islam, these practices are as our Ibadah or worship that is the aim of life as a Muslim. This shows that Islam is a way of life that is not only associated to faith and belief, but it emphasizes good practices and relationships with others.